Modeling of insolvency risk in health sector companies using logit models [Modelación del riesgo de insolvencia en empresas del sector salud empleando modelos logit] (2018)
This article shows the prediction of the level of insolvency in companies that are not listed on the stock exchange belonging to the health sector for one and two years in advance, using the multiple logistic regression analysis based on indicators of liquidity, indebtedness, financial structure and pro_tability. The period 2010@@@2013 is taken as a reference for a sample of 3,930 companies categorized by size (large, medium, small and micro), and classified by their level of high, medium and low insolvency risk. The success results of the models are between 70% and 80% for each of the years, validating the results obtained throughout the study. © 2019, Universidad Pablo de Olavide.